2017
DOI: 10.15252/embj.201796541
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4K20 tri‐methylation at late‐firing origins ensures timely heterochromatin replication

Abstract: Among other targets, the protein lysine methyltransferase PR-Set7 induces histone H4 lysine 20 monomethylation (H4K20me1), which is the substrate for further methylation by the Suv4-20h methyltransferase. Although these enzymes have been implicated in control of replication origins, the specific contribution of H4K20 methylation to DNA replication remains unclear. Here, we show that H4K20 mutation in mammalian cells, unlike in , partially impairs S-phase progression and protects from DNA re-replication induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 62 publications
(150 reference statements)
7
72
0
Order By: Relevance
“…We show that H4K20me3 is present in a subset of non-genic late replicating initiation zones, which are enriched in ORC/ MCM binding. This confirms our previous finding that H4K20me3-mediated ORC-DNA binding enhances origin activity in certain environments 18, 32 . Finally, we find that the global density of ORC highly correlates with replication timing, an effect observed less prominently for MCM.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…We show that H4K20me3 is present in a subset of non-genic late replicating initiation zones, which are enriched in ORC/ MCM binding. This confirms our previous finding that H4K20me3-mediated ORC-DNA binding enhances origin activity in certain environments 18, 32 . Finally, we find that the global density of ORC highly correlates with replication timing, an effect observed less prominently for MCM.…”
supporting
confidence: 92%
“…In multicellular organisms, replication initiates from flexible locations and no common consensus element for origin selection and activation has yet been identified. It is generally believed that chromatin features including histone modifications, nucleosome dynamics and DNA modifications contribute to origin specification 1, 16, 17 , including H4K20me3 that supports the licensing of a subset of late replicating origins in heterochromatin 18 . Thus, changing environmental conditions, DNA damage and the development status of each cell are integrated into highly dynamic local chromatin profiles, which influence the plasticity of origin selection 1 .…”
mentioning
confidence: 99%
“…The monomethyltransferase SETD8 (also known as PR‐Set7) catalyzes H4K20me1. Depleting SETD8 causes defects in origin licensing, whereas inappropriate SETD8 expression in S phase promotes unregulated relicensing and rereplication . Subsequent trimethylation of histone H4K20, which requires H4K20me1 as a substrate, ensures that late‐firing origins are activated during S phase.…”
Section: G1: Preparing Dna For S Phasementioning
confidence: 99%
“…A recent study investigated the role of H4K20me marks in controlling late-firing origins. It showed that the conversion of K20me1 to K20me3 enhances ORCA recruitment and MCM loading at already defined origins required for the correct replication of heterochromatin (Brustel et al, 2017). Interestingly, the loss of Su4-20h, which is responsible for this methylation, delays RT for 15% of the mouse genome.…”
Section: Early Replicators Can Advance Replication Timing Locally In mentioning
confidence: 99%